Microporous activated carbon from pinewood and wheat straw by microwave-assisted KOH treatment for the adsorption of toluene and acetone vapors. Issue 45 (20th May 2015) - Mao, Haiyan; Zhou, Dingguo; Hashisho, Zaher; Wang, Sunguo; Chen, Heng; Wang, Haiyan (Helena); Lashaki, Masoud Jahandar
<x xml:space="preserve">Abstract</x> Pore size distribution of raw char, pinewood char activated with KOH/char mass ratios 0.5, 1.5 and 3.0 was explored.